Putnam’s Problem of the Robot and Extended Minds - Berk, Jacob (Stance: an international undergraduate philosophy journal, 2022)
In this paper, I consider Hilary Putnam’s argument for the prima facie acceptance of robotic consciousness as deserving the status of mind. I argue that such an extension of consciousness renders the category fun- damentally unintelligible, and we should instead understand robots as integral products of an extended human conscious- ness. To this end, I propose a test from con- ceptual object permanence, which can be applied not just to robots, but to the in- numerable artifacts of consciousness that texture our existences.